Clinical Effects of Topical Preparation of Dexamethasone Propionate for Intractable Skin Diseases - CHANOKI, Miyako; MAEKAWA, Naoki; SOMEDA, Yukiko; SUZUKI, Shinsuke; SHOJI, Akinobu; SHIMOTOGE, Masashi; KATOH, Haruhisa; YOSHIOKA, Keiko; HAMADA, Toshio; ISHII, Masamitsu; NAKANISHI, Takeshi; KITAJIMA, Jun-ichi; et al. (Skin research, 1993)
We evaluated clinical effects of dexamethasone propionate ointment and cream for 41 male and 34 female with intractable skin diseases, including idiopathic pigmented purpura (20 cases), hypertrophic scar or keloid (15 cases) and so on. The efficacy of the drug was following: cure in 11 (14.7%), exellent in 19 (25.3%), good in 18 (24%), fair in 20 (26.7%) and poor in 7 cases (9.3%). The efficacy rates were 62.5% for the ointment and 66.7% for the cream, totaling 64.0%. An adverse reaction was seen in four patients; folliculitis, pruritus, skin atrophy and irritation, respectively. All reactions were, however, mild and transient. The results of our study support efficacy and safety of dexamethasone propionate in management of intractable skin diseases.